An ANFIS Control Approach of a Bi-Directional Buck-Boost used for a Battery Charger - Tsiloavy Randjaka; Solofanja Jeannie Rajonirina; F. Philibert Andriniriniaimalaza; Jean Nirinarison Razafinjaka (International Journal of Engineering and Management Research, 2022)
In this work, a neuro-fuzzy regulator based on ANFIS is designed for the current control of a Bidirectional Buck-Boost chopper battery charger. First, a PI regulator is used in the control loop. Data from the PI regulator is extracted and then used to train ANFIS. The performances of the two PI and neuro-fuzzy commands were evaluated under the MATLAB/SIMULINK environment. According to the simulation results, it was found that the neuro-fuzzy regulator ANFIS is more effective in improving the current response by reducing the response time. In conclusion, the neuro-fuzzy control gives a better performance compared to the PI control.